2018
DOI: 10.3390/toxins10010041
|View full text |Cite
|
Sign up to set email alerts
|

Transketolase Is Identified as a Target of Herbicidal Substance α-Terthienyl by Proteomics

Abstract: α-terthienyl is a natural phytotoxin isolated originally from Flaveria bidentis (L.) Kuntze. The bioassay presented here shows the strong herbicidal activity of α-terthienyl on Digitaria sanguinalis, Arabidopsis thaliana and Chlamydomonas reinhardtii. The α-terthienyl-induced response of A. thaliana at the protein level was analyzed at different times. Changes in the protein expression profiles were analyzed by two-dimensional gel electrophoresis and liquid chromatography tandem mass spectrometry (LC-MS/MS) ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…A remarkable lack of correlation between transcriptome and proteome results was observed, although the lack of correspondence between transcriptome and proteome data could be due to multiple factors (Duke et al 2013; Narayanan and Van de Ven 2014; Payne 2015). Similarly, Zhao et al (2018) found decreases in the transketolase protein of Arabidopsis treated with α-terthienyl, but the gene for this enzyme was upregulated by the same treatment. They hypothesized that the decrease in protein was due to direct interaction with α-terthienyl, which resulted in upregulation of the gene to compensate.…”
Section: Limitations Conclusion and Future Directionsmentioning
confidence: 83%
See 1 more Smart Citation
“…A remarkable lack of correlation between transcriptome and proteome results was observed, although the lack of correspondence between transcriptome and proteome data could be due to multiple factors (Duke et al 2013; Narayanan and Van de Ven 2014; Payne 2015). Similarly, Zhao et al (2018) found decreases in the transketolase protein of Arabidopsis treated with α-terthienyl, but the gene for this enzyme was upregulated by the same treatment. They hypothesized that the decrease in protein was due to direct interaction with α-terthienyl, which resulted in upregulation of the gene to compensate.…”
Section: Limitations Conclusion and Future Directionsmentioning
confidence: 83%
“…Likewise, amiprophos-methyl, a herbicide that affects microtubule function, had effects on proteins associated with diverse physiological and biochemical processes but not directly associated with tubulin (Wang et al 2011). More recently, the natural phytotoxin α-terthienyl was found to affect 16 proteins associated with energy transduction, of which the transketolase protein was greatly reduced (Zhao et al 2018). A transketolase-altered mutant was less sensitive to the phytotoxin, and the enzyme from the mutant was less inhibited by the compound.…”
Section: Integrated Omics Approaches To Understanding Phytotoxin Moamentioning
confidence: 99%
“…Transketolase is a target for herbicide design [ 3 , 11 ], and it has a highly conserved homologous domain in higher plants and fungi. A total of 25 candidate molecules with binding affinities lower than −8.5 kcal/mol ( Table S1 ) were obtained from 1 million ZINC compounds after virtual screening.…”
Section: Resultsmentioning
confidence: 99%
“…TKT is a key enzyme in the Calvin cycle of photosynthesis and the pentose phosphate pathway in all organisms. The low amounts of TKT should repress the efficiency of Calvin cycle and pentose phosphate pathway, hindering the photosynthesis rate and resulting in plant death [58]. Thus, the TKT plays an important role in plant defense and growth.…”
Section: Discussionmentioning
confidence: 99%